The Analisis Prediksi Kebangkrutan Pada PT. Ferdinan Mandiri di Masa Pandemi Covid-19 - Umi kalsum Umi (Journal Research of Economic and Bussiness, 2023)
This study aims to analyze bankruptcy predictions at PT. Ferdinan Mandiri with conditions before Covid-19 and two years after covid-19 by looking at financial ratios and the Altman Z-Score to predict bankruptcy. The analysis technique in this study uses quantitative descriptive. The population in this study is PT. Ferdinan Mandiri engaged in services. The results of this study indicate that the profitability ratio proxied by ROA is in a negative position because the company suffered losses after the impact of covid-19. The ROA value at PT. Ferdinand Mandiri is not very good because it is very low compared to industry standards. The liquidity ratio, which is proxied by the Current ratio, shows that there is a decrease in the current ratio, so that the company experiences liquidity problems to pay off short-term debt. The solvency ratio which is proportional to the debt to equity ratio shows that there is an increase in this ratio. The results show that the company's retained earnings are getting smaller due to losses, so the company's equity has fallen sharply. Based on the Altman Z-Score analysis, the company's condition has been in a position of potential bankruptcy since two years after covid-19.